Evaluating Asymmetric Dimethylarginine (ADMA) as a Biomarker for Preeclampsia: A Meta-Analysis - Bansal, Abhishek; P. Hadimani, Chetana.; B Patil, Sadanand; Zuki Bin Nik Lah, Nik Ahmad (Journal of Neonatal Surgery, 2025)
Background: Preeclampsia (PE) is a serious pregnancy-related disorder characterized by hypertension, endothelial dysfunction, and multi-organ involvement. Despite advances in understanding its pathophysiology, early diagnosis and reliable biomarkers remain critical challenges. Asymmetric dimethylarginine (ADMA) is a natural inhibitor of nitric oxide synthase (NOS) that has been implicated in endothelial dysfunction, a key feature of PE. This study aims to evaluate the potential of ADMA as an early biomarker for the detection and assessment of preeclampsia. Methods: This systematic review and meta-analysis included 16 observational studies examining the association between serum ADMA levels and preeclampsia. Data from 767 women with PE and 896 healthy controls were analyzed to determine the mean difference in ADMA levels between the two groups. The analysis followed PRISMA guidelines, and heterogeneity was assessed using the I² statistic. Results: The pooled analysis revealed that serum ADMA levels were significantly higher in women with preeclampsia compared to healthy pregnant controls (mean difference = 0.38 µmol/L, 95% CI: 0.11–0.65 µmol/L, p = 0.01). Significant heterogeneity (I² = 99.9%) was observed across studies. Funnel plots indicated no significant publication bias. Conclusion: Elevated ADMA levels are associated with preeclampsia and may serve as a promising biomarker for early detection and disease severity evaluation. Despite significant heterogeneity across studies, the findings suggest ADMA's potential role in the pathophysiology of PE, particularly in endothelial dysfunction. Further prospective studies and standardization of measurement techniques are required to confirm ADMA’s clinical utility in preeclampsia diagnosis and management.